Where Is the Carbon Premium? Global Performance of Green and Brown Stocks - Michael D. Bauer; Daniel Huber; Glenn D. Rudebusch; Ole Wilms (Center for Economic Studies and ifo Institute (CESifo), 2023)
The relative equity pricing of more climate-friendly ("green") versus less climate-friendly ("brown") companies is an open question in climate finance. Previous research comes to conflicting conclusions, documenting either a "carbon premium" with brown stocks yielding higher returns, or the opposite, with green stocks outperforming brown. This paper provides new international evidence on this issue for a range of methodologies. Using carbon dioxide (CO2) emissions as reported by companies to measure their greenness, we document that green stocks across the G7 have generally provided higher returns than brown stocks for much of the past decade. We also try to reconcile our findings with previous work, and we provide some results for early 2022 that show that brown stocks outperformed green ones during the energy crisis.
Keywords: G11; G12; Q54; 330; climate risk; transition risk; carbon emissions; green stocks; brown stocks